Implementasi Pendidikan Karakter pada Sekolah Inklusif di SDN Cisarua Kota Sukabumi - Sidik, Ridwan Ahmad; Rahayu, Ucu; Rokayah (MAARIF, 2023)
This research aims to describe the implementation of character education in inclusive schools at SDN Cisarua, Sukabumi City. The aspects observed in the implementation of character education include learning, example, strengthening, and habituation. This is qualitative research with a descriptive qualitative research design. The subjects of this research included school principals, class teachers, and students with special needs (ABK). The data collection techniques used in this research are interviews, observation, and documentation studies. This research data was analyzed using data reduction steps, data presentation, and drawing conclusions. Data validity checking technique using triangulation of techniques and sources the results of the research show that the principal’s policy and the role of the class teacher have been instilled in students in their class, especially those with special needs, through learning, example, strengthening, and habituation. In implementing learning, teachers emphasize instilling the character values of tolerance and caring. The teacher does this in learning by instilling concepts through explanations, discussing moral issues, stories, active learning, and collaborative methods. Apart from that, teachers also set examples in attitudes and actions, give awards, provide individual assistance, and familiarize students with mingling with friends with special needs, both in the classroom and outside the classroom.